(untitled) (IJM: Journal of Multidisiplinary, 2025)
This study aims to analyze the close relationship between Srivijaya and the maritime trade routes connecting Southeast Asia with India and China, and how diplomacy built by Srivijaya helped strengthen its position as a center of Buddhist education in the region. The main sources used in this study include the travel notes of the monk I-Tsing, inscriptions found at various Srivijaya sites, and archaeological remains that provide a picture of social and religious life at that time. Based on the analysis of these sources, this study shows that Srivijaya not only played a role as a maritime trade center connecting various kingdoms in Asia, but also as a gathering place for monks and students from various parts of the world to deepen their Buddhist teachings. The existence of Srivijaya as a center of Buddhist education is reflected in its close relationship with various Buddhist education centers in India, such as Nalanda, as well as with kingdoms in China. In addition, Srivijaya has also been proven to have a very important role in forming a diplomatic network between countries that supports the spread of Buddhist teachings in the archipelago and its surrounding areas. Through this diplomatic relationship, Srivijaya succeeded in building a strong influence in the spread of Buddhism, which later developed into an integral part of culture in Southeast Asia.